COMPARATIVE CHONDROPROTECTIVE EFFECTS OF INTRA-ARTICULAR HYALURONIC ACID AND TRIAMCINOLONE IN MURINE MODEL OF OSTEOARTHRITIS - Ishaq, Noaman; Gul, Shahzad; Gul, Mahwish; Ata, Nausheen; Batool, Saba; Mehdi, Quratulain (Journal of Ayub Medical College Abbottabad, 2022)
Osteoarthritis is a heterogeneous disease of joints that affects mainly older population. Definitive cure of osteoarthritis is still undiscovered. This study was designed to evaluate and compare the chondroprotective effects of hyaluronic acid and triamcinolone in murine model of osteoarthritis. Methods: This Laboratory based experimental study was carried out in Pharmacology Department, Army Medical College Rawalpindi, from April-June 2019. Osteoarthritis was induced by medial menisectomy and anterior cruciate ligament resectioning of knee joints of twenty-four rats which were then divided into three groups with eight rats in each. Group I, II and III were named control, hyaluronic acid and triamcinolone groups respectively, which were given intra-articular injections of these drugs once weekly for four consecutive weeks and then gait pattern was scored. Animals were sacrificed thereafter and samples were collected for histopathological analysis. Results: Comparison of gait score of control, hyaluronic acid and triamcinolone groups exhibited a p value of <0.01 while intergroup comparison between group I and II, group I and III and group II and III depicted p value of <0.001, 0.016 and 0.003 respectively. Likewise, collective histopathological analysis of the three groups showed p value of <0.01 while intergroup comparison of group I and II, group I and III and group II and III showed p value of <0.001 for all. Conclusion: Comparison of control group with treatment groups proved chondroprotective effects of hyaluronic acid and triamcinolone. Additionally, hyaluronic acid proved to provide better chondroprotection as compared to triamcinolone.